Diseño y construcción de un elevador móvil electrohidráulico tipo tijera con capacidad de carga de 500 kilogramos para el mantenimiento de maquinaria - Almeida García, Carlos Andrés (2016)
This final project has three chapters, which explains the design and construction of a mobile scissors electro hydraulic elevator for machinery maintenance in confined space. The elevator has a 500 Kilograms of load capacity and a height of 2 meters. The first and second chapters explain some types of elevators, which will be evaluated through the scoring method to evaluate the best alternative, becoming a great help for the machine design. Additionally, it has technical definitions and specify the main components of the equipment. The third chapter describes the design calculation and materials selection for the construction of each element that integrates the machine; MD Solid and Solid Works programs were used for testing materials, validating mathematical processes already mentioned and reducing error margin of the final product. At the end of the project, chapter fourth explains the financial component, key point where the direct and indirect cost are determining factors for the feasibility and subsequent construction of the electro hydraulic scissors type elevator.